Design and Development of 3-Dimensional Model of Human Circulatory System to Teach a Concept of Biology in Senior Secondary Schools - Babalola, Ebenezer Omolafe (Universitas Pendidikan Indonesia (UPI), 2022)
Instructional resources guarantee maximum value and effectiveness in the teaching and learning process. The instrument of instruction is communication which must be skillfully designed and developed if the objective of the instruction is to be accomplished. Models are a direct replica of real objects or figures. They are made in place of the original figure or object and used as such in place of the original. Inability to have access to mammalian internal organs is one of the challenges in teaching some concepts in Biology. Hence, we need to develop a 3-dimensional model of the human circulatory system to teach a concept in Biology. The findings revealed that the 3-dimensional automated model of the human circulatory system was successfully developed with materials sourced from the environment. Such materials include Plaster of Paris (POP), Top gum, White Cement, Car Paint (white), Acrylic Paint (Blue and Red), Tissue Paper, Binding Wire, Painting Brush, Silicon Gum, Sandpaper. This study recommended among others that management of secondary schools should make provision for the local 3-D model to be used as teaching aids for effective instructional delivery in their respective schools.